Rice trade in a changing climate of national adaptation plans - Schletz, Marco C. (2014)
Adaptation strategies and policies often fail to take account of climate change impacts and their feedbacks in one country which have ‘indirect impacts’ for other countries and the global system. This thesis examines the risks posed by climate change to global rice trade and the possible impact on food security in nations dependent on rice imports. Rice is a staple food for half of the world's population and the most important calorie source for many of the world's poor. This thesis develops a method to assess these risks for four nations depending on rice imports: Senegal, South Korea, the United Arab Emirates and the United Kingdom. Several data sets, such as rice trade data, climate scenario data and rice consumption data, are combined into a multi-step risk assessment. Thereby, this study examines the possible dynamics between climate change impacts in trade partner countries, namely in key rice producing countries in Asia, and the repercussions on domestic food security in rice import dependent countries. It further investigates the extent and how national adaptation plans acknowledge or address these indirect risks. The thesis finds that all four case studies countries are sensitive to indirect climate change impacts on rice imports. The comparison between case study risks identifies the systemic nature of trade related climate risks. This means that risks can be magnified when multiple importing countries are exposed to the same risk and measures exacerbate the effects for other countries. This systemic nature of risk to the rice market raises the importance of internationally coordinated adaptation between countries to the systemic risk to enhance the resilience of food systems.